Dermatopathology - Brehmer-Andersson, Eva. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The book describes the principles of histopathologic patterns in selected acquired skin diseases, together with short clinical descriptions and case reports. The underlying, or possible underlying, mechanisms are elucidated, and controversial concepts  are discussed. To facilitate the understanding of underlying mechanisms, the first chapters of the book comprise summaries of basic histology of lymphatics and blood vessels, relevant parts of general pathology, immunology, and molecular cell biology.  The histopathological patterns are demonstrated by means of 420 micrographs in shades of gray. .